An investigation on communication style for school administrators in Sekolah Kebangsaan Islah, Kota Bharu / Norhisham Mohd Kasim - Mohd Kasim, Norhisham (2013)
Communication is an important element considered in the life and in the context o f management and administration, it is considered a matter that should be taken care o f by each administrator. Therefore the communication style o f each school administrators is needed to be identified in shaping educational leadership. Communication style is defined as a set o f interpersonal behavior that can be used in a specific situation. Thus the administrator in education plays a very important role. They need to ensure that every action and decision is made to create a quality management system. To be a good administrator is not an easy thing, but i f an administrator can learn the basic things that should be inherent in a leader, it will be more convenient and enjoyable in everyday work. This study presents the finding o f a study to investigate the communication styles o f administrators in Sekolah Kebangsaan Islah. This study consists o f 4 research question to identify the types o f communication styles that exist between the administrator, the administrator o f communication different styles according to their gender, identify the different styles o f communication between senior and junior administrators and find out the extent to which the effect o f the level o f education administrators on communication styles. Previous studies about communication styles are also discussed in this study. It's a bit much to support and help the results in this study. It is also hoped that this study will improve the quality o f administrative communication thus creating a quality management. There are 30 teachers administrators were selected to answer the questionnaire and 7 teachers administrators to answer some interview questions in this study.The finding o f this study indicate that there is a assertive style o f communication between teachers administrators in the Sekolah Kebangsaan Islah, senior administrators who are more aggressive than a junior administrator, males are more assertive than female administrators and education level between the administrator does not have any effect on the person's communication style administrator. This study concluded that everyone including administrators teachers have different communication styles and influenced by gender, age and experience. Therefore understand the communication styles that exist in the individual and others is important in the management o f an organization. Recommendations and suggestions o f this study is that we need to understand the underlying individual perceptions when communicating with others in the context o f the organization.